Teologi Toleransi; Dari Toleransi Recognize menuju Toleransi Nilai - Imam Hanafi (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2019)
This article wants to redefine tolerance, it also wants to show that religious plurality becomes a necessity that cannot be sued. In addition, this article wants to see the negative side of the emergence of a single logical reasoning on religious truth. This topic is examined using a qualitative-descriptive approach, emphasizing the importance of humans being actively tolerant, reviving values in the natural diversity of the country. At the end of this article, the author also wants to show that plurality as a necessity, can be read from theological perspective. Therefore, the reconstruction of Islamic theology is needed to re-read the meaning of true tolerance.